2018
DOI: 10.1364/ol.43.000478
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized compound pattern and pulsation of dissipative solitons in a passively mode-locked fiber laser

Abstract: We experimentally observe soliton self-organization and pulsation in a passively mode-locked fiber laser. The optomechanical interaction in the optical fiber is key to the formation of equidistant soliton bunches. These solitons simultaneously undergo a pulsation process with a period corresponding to tens of the cavity round trip time. Using the dispersive Fourier transformation technique, we find that the Kelly sidebands in the shot-to-shot spectra appear periodically, synchronizing with the pulsation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…In addition to their widespread use as sources of ultrashort pulses for many applications, mode-locked lasers constitute an ideal platform for the fundamental exploration of complex dissipative nonlinear dynamics. Various notable nonlinear phenomena have been observed in mode-locked lasers, including rogue waves (13,14), soliton molecules and molecular complexes (15)(16)(17)(18), pulsations of soliton bunches (19), and soliton explosions (20)(21)(22). Furthermore, a recent theoretical work using the master equation approach (23) has showed that there are regimes of operation in which laser oscillators may generate breathing solitons with large ratios of maximal to minimal energies in each period of pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their widespread use as sources of ultrashort pulses for many applications, mode-locked lasers constitute an ideal platform for the fundamental exploration of complex dissipative nonlinear dynamics. Various notable nonlinear phenomena have been observed in mode-locked lasers, including rogue waves (13,14), soliton molecules and molecular complexes (15)(16)(17)(18), pulsations of soliton bunches (19), and soliton explosions (20)(21)(22). Furthermore, a recent theoretical work using the master equation approach (23) has showed that there are regimes of operation in which laser oscillators may generate breathing solitons with large ratios of maximal to minimal energies in each period of pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…The recently developed time-stretch dispersive Fourier transform (TS-DFT) technique provides a powerful way for real-time, single-shot measurements of ultrafast phenomena [23]. This technique helps scientists to experimentally resolve the evolution of femtosecond soliton molecules [24][25][26], the dynamics of soliton explosions [27], and pulsating solitons [28,29]. The TS-DFT technique was also employed to measure the build-up process of solitons [2,25,[30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…By using the TS-DFT technique, they found the spacing of solitons in one bunch is different, while their phase relation is fixed. Soliton pulsation was also observed, and Kelly sideband appeared with the pulsating period [246]. The study on the dynamics of soliton molecule brings new perspectives for ultrafast transient dynamics and opens new pathways of pulses evolution and interaction that will reveal the physics of solitons dynamics in nonlinear system.…”
Section: Buildup Dynamics Of Soliton Moleculesmentioning
confidence: 89%